2022
DOI: 10.3389/fmicb.2022.829152
|View full text |Cite
|
Sign up to set email alerts
|

Response of Fungal Sub-Communities in a Maize-Wheat Rotation Field Subjected to Long-Term Conservation Tillage Management

Abstract: Conservation tillage is an advanced agricultural technology that seeks to minimize soil disturbance by reducing, or even eliminating tillage. Straw or stubble mulching in conservation tillage systems help to increase crop yield, maintain biodiversity and increase levels of exogenous nutrients, all of which may influence the structure of fungal communities in the soil. Currently, however, the assembly processes and co-occurrence patterns of fungal sub-communities remain unknown. In this paper, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…However, in this study, the relative abundance of phyla Acidobacteria and Firmicutes decreased with the application of straw retention in tillage and no-tillage treatment ( Supplementary Figure S1 ). The reduction in acidobacteria might be due to the high level of available carbon sources as it is reported that the relative abundance of acidobacteria was higher in the low level of carbon (Fierer et al, 2007 ), while in this study, total organic carbon was relatively higher with straw retention application (Zhang et al, 2022 ). The relative abundance of the genus Lactococcus, Bacillus , and Solibacillus ( Firmicutes ) and unclassified _o_ iii1-15 ( Actinobacteria ) decreased in tillage with straw retention treatment ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…However, in this study, the relative abundance of phyla Acidobacteria and Firmicutes decreased with the application of straw retention in tillage and no-tillage treatment ( Supplementary Figure S1 ). The reduction in acidobacteria might be due to the high level of available carbon sources as it is reported that the relative abundance of acidobacteria was higher in the low level of carbon (Fierer et al, 2007 ), while in this study, total organic carbon was relatively higher with straw retention application (Zhang et al, 2022 ). The relative abundance of the genus Lactococcus, Bacillus , and Solibacillus ( Firmicutes ) and unclassified _o_ iii1-15 ( Actinobacteria ) decreased in tillage with straw retention treatment ( Figure 2 ).…”
Section: Discussionmentioning
confidence: 48%
“…We explained the experimental site and sampling strategy in our recently published study (Zhang et al, 2022 ). In brief, the long-term conservation field was commenced in 2006 and based on a completely randomized block design with three replications.…”
Section: Methodsmentioning
confidence: 99%
“…The soil pH, organic matter (SOM), total nitrogen (TN), total phosphorus (TP), available phosphorus (AP), total potassium (TK), and available potassium (AK) were measured as previously described [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies, however, have shown that rare fungal taxa, which likewise include diverse genes and functions [ 14 ], can serve as an equally valuable genetic repository compared to the more abundant and metabolically active strains, and these rare taxa also play an important role in community function and stability [ 13 ]. Furthermore, abundant and rare sub-communities that have different ecological strategies [ 15 ] mean that the structure of those sub-communities is influenced by different controlling factors or ecological processes [ 16 , 17 ]. Compared to abundant taxa, rare taxa have a narrower ecological niche width and lower competitive ability, and are more influenced by external factors, while abundant taxa tend to have a wider ecological niche width and higher competitive ability and are less influenced by external factors [ 15 ].…”
Section: Introductionmentioning
confidence: 99%